Analysis of Consumer Preferences Towards the Decision to Purchase Facial Moisturizer Cosmetic Preparations (Among Ft UNJ Students) - Diah Pricilia Permata Putri; Mari Okatini Armandari; Neneng Siti Silfi Ambarwati (Jurnal Multidisiplin Sahombu, 2026)
This study aims to analyze consumer preferences regarding purchasing decisions for facial moisturizer cosmetics among students of the Faculty of Engineering, State University of Jakarta. The skin is a complex and sensitive protective organ of the body, so proper skin care is crucial for maintaining health and appearance (Hartopo & Hajjah, 2020; Menaldi et al., 2019). Cosmetics, including facial moisturizers, play a role in maintaining skin hydration, texture, and elasticity (Trenggono & Fatma, 2007). Consumer preferences are influenced by product attributes, brand, price, access and distribution, and social factors (Kotler & Keller, 2016). The research method used a quantitative descriptive approach with a population of female students of the Faculty of Engineering, UNJ and a sample of 100 respondents through purposive sampling. Data collection was carried out using a Likert-based questionnaire, analyzed with descriptive statistics and multiple linear regression. The results showed that simultaneously, consumer preference variables did not significantly influence purchasing decisions. However, partially, product attributes were proven to have a significant influence, while brand, price, access and distribution, and social factors did not show a significant influence. These findings confirm that students consider product quality as a primary factor in choosing a facial moisturizer, and indicate the need to develop other variables for a more comprehensive understanding of consumer behavior.